MANAJEMEN MUTU KELAS DALAM MENCIPTAKAN LINGKUNGAN BELAJAR KONDUSIF DI SDN PALIPURNA - Supyan Sauri; Farhan Hudori Abaz; Ai Citra Susanti; Nur Endah Sariningsih; Dini Astuti; Cucu Juhariah (STKIP Subang, 2025)
This study aims to describe the implementation of classroom quality management in creating a conducive learning environment at SDN Palipurna through the PDCA (Plan–Do–Check–Act) cycle approach. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the principal and teachers, while the research object focused on the planning, implementation, evaluation, and follow-up of classroom quality management. Data were collected through observation, interviews, and documentation study. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that at the planning stage, teachers systematically prepared classroom management plans by determining objectives, strategies, and classroom rules that support the creation of a conducive learning environment. At the implementation stage, teachers consistently applied classroom management through managing learning interactions, organizing the classroom environment, and providing positive reinforcement to students. At the evaluation stage, teachers carried out reflection and assessment of classroom conditions and learning processes to identify strengths and obstacles. Furthermore, at the follow-up stage, teachers made improvements and refinements to classroom management strategies based on the evaluation results. Overall, the implementation of classroom quality management through the PDCA cycle was proven to be effective in creating a safe, comfortable, orderly, and enjoyable learning environment, thereby supporting the improvement of learning quality at SDN Palipurna.